Fabrication and characterization of flat sheet and hollow fiber mixed matrix membrane for gas separation [compact disc] - 375726 Tutuk Djoko Kusworo; Ahmad Fauzi Ismail, 1966- (2008)
Thesis PhD (Doktor Falsafah (Kejuruteraan Gas)) - Universiti Teknologi Malaysia, 2008